(untitled) (IPS Journal of Public Health, 2025)
Cervical cancer screening is a preventive health intervention targeted at women at risk of developing cervical cancer. This study aimed to assess the acceptance and practice of cervical cancer screening among female students of the Rivers State College of Health Science and Management Technology, Port Harcourt. A descriptive survey design was adopted, and a sample size of 220 was determined using Fisher’s formula. Findings revealed that the majority (86.8%) of respondents were aware that cervical cancer is the most common cancer of the female reproductive tract, while 91.8% identified Human Papillomavirus (HPV) as its primary cause. However, 85.9% disagreed that cervical cancer screening (CCS) should form part of routine examinations for women of menopausal and childbearing age, and 55.9% believed that women who maintain good genital hygiene and a single sexual partner do not require CCS. All respondents (100%) agreed that the absence of a national free cervical screening program contributes to the high prevalence of cervical cancer in Nigeria. Despite this awareness, 93.2% indicated that they do not look forward to undergoing cervical cancer screening, although 73.2% expressed interest in studying more about CCS to improve their knowledge of womanhood. Based on these findings, the study concludes that the attitude and practice of female health students towards cervical cancer screening are poor, despite their training in a health institution. The results also suggest that profession or department has little influence on attitudes and practices, as responses were similar across groups. It is therefore recommended that cervical cancer screening initiatives be targeted at women who have never undergone Pap smear testing, as well as all other eligible women